Pelatihan Interpersonal Skill “Bagaimana Memenangkan Hati Orang Lain Dan Mempengaruhi Mereka” Bagi Klien Pemasyarakatan Di Balai Pemasyarakatan (BAPAS) Kelas I Tangerang - Yoyo, Toni (LP3kM Universitas Buddhi Dharma, 2022)
To reduce the number of crimes or criminal acts, various sanctions are determined by the state, one of which is corporal punishment. Sanctions of imprisonment by the state for perpetrators of crimes or criminal acts aim to provide a deterrent effect to the person concerned and other people. Reintegration or social reintegration is a process in which a person sentenced to corporal confinement according to state law, after fulfilling certain requirements, returns to life in society. This community service activity was carried out in the form of training, which was held in the Class 1 Tangerang Correctional Center (Bapas). The training participants were correctional clients of the Bapas. The implementation method used was participatory. Based on this method, the training participants were invited to be actively involved in the delivery and discussion of the training materials. The training given to correctional clients at the Class 1 Tangerang Correctional Center (Bapas) was interpersonal skills training. The aim of the training is to provide correctional clients with the knowledge and ability to build good relationships with other people in the community.